2008
DOI: 10.1021/jp809177n
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependence of Cubic to Trigonal Structural Distortion in Silver Micro- and Nanocrystals under High Pressure

Abstract: Silver micro-and nanocrystals with sizes of -2-3.5 llm and -50-100 nm were uniaxially compressed under nonhydrostatic pressures (strong deviatoric stress) up to -30 GPa at room temperature in a symmetric diamond-anvil cell and studied in situ using angle-dispersive synchrotron X-ray diffraction. A cubic to trigonal structural distortion along a 3-fold rotational axis was discovered by careful and comprehensive analysis of the apparent lattice parameter and full width at half maximum, which are strongly depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Mechanical property. As discussed here and in previous work [12][13][14][15][16]18 , high-pressure stress can effectively induce Ag microstructure phase transformations and potentially manipulate the mechanical stability of Ag nanoparticles. Gu et al 12 found an unexpected high stiffness of Ag and gold (Au) nanoparticles under high pressure.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Mechanical property. As discussed here and in previous work [12][13][14][15][16]18 , high-pressure stress can effectively induce Ag microstructure phase transformations and potentially manipulate the mechanical stability of Ag nanoparticles. Gu et al 12 found an unexpected high stiffness of Ag and gold (Au) nanoparticles under high pressure.…”
Section: Resultssupporting
confidence: 55%
“…Many chemical methods use such defect structures (also the most reactive sites) to achieve oriented growth of Ag nanostructures; for example, oriented attachment was used to grow chain-like Ag nanostructures 11 . It has been shown elsewhere that an external stress induced by high-pressure compression can alter the mechanism of defect motion in atomic lattices through induced phase transformations [12][13][14] . Depending on the pressure condition, different Ag phase and structural transformations were observed: under hydrostatic pressure up to 10 GPa, Ag nanoparticles with sizes of 5-10 nm underwent a reversible, linear, pressure-dependent structural transformation 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the last twod ecades,muche ffort havebeen devoted toinvestigating the opticalpropertiesof silvernanoparticless ynthesized viac hemicalreductions [11,12], gas condensation [13], laserirradiation [14], sonochemicaldeposition [15]a nd nanostructured templates [7].All these advanceshaveadvanced scientificknowledge of the nature of silvernanoparticles.Aheadamong others,c hemicalreduction techniquesofferanovel,simple proceduref ort he synthesisof silvernanoparticlescompared toothers which required high production cost and moreprocess timing becausetheyu sed complexs et-upsfors ynthesis [16][17][18]. Well-defined particle size,shape and sized istribution are controlled byjudiciouslychoosing the reaction temperature,the orderof addition of reagents and the ratio of protectiveagent/metalcompound whicharethe factors actuallygovernthe plasmonresonancee xcitation of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…This reversible distortion is consistent with a mechanism that considers the bond‐length distribution in idealized, multiply twinned icosahedral particles. Guo et al compared the Ag nanocrystals (with size of ≈50–100 nm) and microcrystals (with size of ≈2–3.5 μm) with irregular morphologies under uniaxial compression (i.e., nonhydrostatic pressure) up to ≈30 GPa, and found a cubic‐to‐trigonal structural distortion along a three‐fold rotational axis of the fcc lattice 14. These studies show an obvious controversy regarding the pressure‐dependent structural variation in Ag nanoparticles.…”
mentioning
confidence: 99%